ANALYSIS OF MAPPING OF THE LEVEL OF FLOOD PRONECTION IN BOJONEGORO REGENCY BASED ON GEOGRAPHIC INFORMATION SYSTEM - Mushthofa, Mushthofa; Qomaruddin, Mochammad (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2023)
Floods are natural disasters that often occur in various parts of the world, especially in flood-prone areas. Floods occur when water from rivers, lakes or seas overflows beyond its holding capacity. Floods can cause great damage to infrastructure, plants, animals and people. To overcome floods that occur frequently every year, it is necessary to map areas prone to flooding accurately and quickly using GIS which can be used to accurately monitor the location and area of ​​the area that is experiencing flooding. This study aims to analyze flood-prone areas and compile maps of flood-prone areas and describe the conditions of flood-prone areas in Bojonegoro Regency based on Geographic Information Systems (GIS). Data processed using GIS include: RBI Map of Bojonegoro Regency, River Map, Soil Type Map, Rainfall Data, Landsat Imagery Data, Flood incident data in Bojonegoro Regency. From the results of data processing, the results of the analysis are as follows: The level of flood-prone areas in Bojonegoro Regency is divided into 3 classes, namely: very vulnerable class of 49,963.671 Ha or around 21.66% of the sub-districts in Bojonegoro including the District: Margomulyo , Ngraho, Padangan, Kasiman, Malo, Purwosari, Trucuk, Kalitidu, Ngasem, Bojonegoro, Kapas, Dander, Balen, Kanor, Baureno, Sumberrejo, Kepohbaru and Gondang. The vulnerable class of 173,162.171 Ha or around 75.05% is in sub-districts including: Margomulyo, Ngraho, Tambakrejo, Kedewan District, Malo, Trucuk, Sekar, Ngambon, Ngasem, Gondang, Bubulan, Dander, Temayang, Sugihwaras and Kedungadem. The non-prone class is 7,580.157 ha or 3.29% in the sub-districts including: Margomulyo, Ngraho, Tambakrejo, Kedewan, Malo, Trucuk, Sekar, Ngambon, Gondang, Temayang, Sugihwaras and Kedungadem. Areas that have a high level of vulnerability are around the Bengawan Solo River which crosses Bojonegoro Regency. This can be caused because the area around the Bengawan Solo River has a height of <25 m and frequent flooding from the upstream and tributaries of the Bengawan Solo River.